THE RELATIONSHIP OF NUTRITION AND SANITATION TO THE EVENT OF STUNTING IN CHILDREN UNDER FIVE IN BOGOR DISTRICT - Tria Astika Endah Permatasari; Yudi Chadirin; Ernirita; Feby Elvira; Bella Arinda Putri (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
The national strategy for accelerating the reduction of stunting in Indonesia reaches 14% in 2024. One of the provinces with stunting prevalence exceeding the national figure is West Java Province (31%). Stunting toddlers experience failure to thrive when their height is less than their age standard. Nutrition and sanitation factors are key indicators as essential criteria that must be achieved at the family level to prevent stunting. This study aimed to examine the relationship between nutrition and sanitation aspects on the incidence of stunting in children under five in Bogor District. The study used a cross-sectional study on 100 childrens aged 0-59 months living in the Bogor district selected by proportional random sampling technique. Stunting was measured using an anthropometric index (body length/height according to age. Measurement of nutrition and sanitation aspects included: 1) Nutrition indicators, namely balanced nutrition practices, quantitative food intake (food frequency questionnaire), 2) sanitation indicators, including personal hygiene practices and availability sanitation facilities. Sociodemographic characteristics were measured using a structured questionnaire. Data were analyzed univariately and bivariate using SPSS version 22.0. The results showed that practicing balanced nutrition was related to stunting in children under five (p = 0.046). Meanwhile, carbohydrate intake, protein intake, and sanitation were not associated with stunting (p=>0.05). Health promotion related to the four principles of balanced nutrition for mothers of children under five is expected to reduce the prevalence of stunting.